Prevalence of associated factors and chronic complications in elderly patients with type 2 diabetes mellitus in the primary care center level III EsSalud - El Agustino - Aguilar Sánchez, Marielena (2019)
Objective: To determine the prevalence of associated factors and chronic complications in elderlypatients with type 2 diabetes mellitus in the Primary Health Care Center Level III Es Salud, El Agustino.Materials and methods: Descriptive study of quantitative type and cross section. The sample consistsof 142 elderly diabetic patients selected by non-probabilistic sampling, according to inclusion andexclusion criteria, to whom an instrument for investigations is applied, proving its validity and reliabilityin a pilot test to 50 patients of similar characteristics. Results: 60.6% presented DM 2 as a familyhistory. According to the body mass index, 34.5% presented normal nutritional status, while 32.4%presented overweight and 29.6% obesity; According to the waist circumference, 68.3% presented ahigh risk of cardiovascular and metabolic diseases. Regarding the practice of healthy habits, 99.3%does not apply to physical exercise and sports; 94.4% presented the management of recreation andfree time; 99.3% do not consume alcohol, coffee or tobacco use; 67.6% presented inadequate eatinghabits. Finally; 43.7% presented urinary infection and 35.2% presented retinopathy. Conclusions: 61% of relatives with DM 2, 62% with overweight and obesity, 68% with high risk of cardiovascular and  metabolic diseases, 36% with inadequate control of HbA1c (≤ 7%), 99% without realization. physicalexercise and sport, 68% presented inadequate eating habits, the most prevalent chronic complicationsare urinary tract infections (44%) and retinopathy (35%); In addition, the factors associated with thecomplications of DM 2, for the most part, are modifiable, therefore there must be adequate control overthese variables, the treatment of adult adults should be focused on these factors.